Emerging concepts in the pathogenesis of the Streptococcus pneumoniae: From nasopharyngeal colonizer to intracellular pathogen. (17th July 2019) - Subramanian, Karthik; Henriques‐Normark, Birgitta; Normark, Staffan
Abstract: Streptococcus pneumoniae (the pneumococcus) is a human respiratory tract pathogen and a major cause of morbidity and mortality globally. Although the pneumococcus is a commensal bacterium that colonizes the nasopharynx, it also causes lethal diseases such as meningitis, sepsis, and pneumonia, especially in immunocompromised patients, in the elderly, and in young children. Due to the acquisition of antibiotic resistance and the emergence of nonvaccine serotypes, the pneumococcus has been classified as one of the priority pathogens for which new antibacterials are urgently required by the World Health Organization, 2017. Understanding molecular mechanisms behind the pathogenesis of pneumococcal infections and bacterial interactions within the host is crucial to developing novel therapeutics. Previously considered to be an extracellular pathogen, it is becoming evident that pneumococci may also occasionally establish intracellular niches within the body to escape immune surveillance and spread within the host. Intracellular survival within host cells also enables pneumococci to resist many antibiotics. Within the host cell, the bacteria exist in unique vacuoles, thereby avoiding degradation by the acidic lysosomes, and modulate the expression of its virulence genes to adapt to the intracellular environment. To invade and survive intracellularly, the pneumococcus utilizes a combination of virulence factors such as pneumolysin (PLY), pneumococcal surface protein A (PspA), pneumococcal adhesion and virulence protein B (PavB), the pilus‐1 adhesin RrgA, pyruvate oxidase (SpxB), and metalloprotease (ZmpB). In this review, we discuss recent findings showing the intracellular persistence of Streptococcus pneumoniae and its underlying mechanisms.